Self-medication by covid-19 in the population of the district of Lircay-Huancavelica in the year 2022 - Curo Yllaconza , Javier Eduardo (2023)
Objective: To estimate the frequency and characteristics of self-medication by COVID-19 in the population of the district of Lircay, in the year 2022. Material and Methods: Basic, cross-sectional, observational, non-experimental design. The sample consisted of 120 customers from 5 pharmacies in Lircay, Huancavelica; selected by non-probabilistic, purposive sampling, who met eligibility criteria; data collection was through a survey, with a structured questionnaire. Results: The arithmetic mean of age was 40.1 years +/-11.2; of the total participants 70% self-medicated when presenting symptoms of COVID-19; the female sex self-medicated more frequently (59.5%); self-medication occurs more in those of secondary education level (44%); the lower the monthly income, the greater the practice of self-medication (47.6%); family members are the ones who give the most advice (29.8%); the age group that self-medicates most frequently is 40 to 49 years of age (29.8%); and azithromycin is the most frequently used drug (32.1%). Conclusion: there is a high prevalence of self-medication for COVID-19 symptoms; therefore, measures should be taken based on health education.